Atlantic Salmon Pre-smolt Survivors of Renibacterium salmoninarum Infection Show Inhibited Cell-Mediated Adaptive Immune Response and a Higher Risk of Death During the Late Stage of Infection at Lower Water Temperatures - Rozas-Serri, Marco; Lobos, Carlos; Correa, Rodolfo; Ildefonso, Ricardo; Vásquez, Jorge; Muñoz, Ariel; Maldonado, Lucerina; Jaramillo, Victoria; Coñuecar, Darling; Oyarzún, Camila; Walker, Romina; Navarrete, Carolina; et al. (Frontiers in Immunology, 2020)
Bacterial kidney disease (BKD) is widespread in many areas of the world and can cause substantial economic losses for the salmon aquaculture industry. The objective of this study was to investigate the pathophysiological response and gene expression profiles related to the immune response at different water temperatures and to identify the best immunopathological biomarkers to define a phenotype of resistance to BKD. The abundance of msa transcripts of R. salmoninarum in the head kidney was significantly higher in infected fish at 11°C. R. salmoninarum induced significantly more severe kidney lesions, anemia and impaired renal function at 11°C. In addition, the expression pattern of the genes related to humoral and cell-mediated immune responses in infected fish at 11°C and 15°C was very similar, although R. salmoninarum induced a significantly greater downregulation of the adaptive immune response genes at the lower water temperature. These results could be due to a suppressed host response directly related to the lowest water temperature and/or associated with a delayed host response related to the lowest water temperature. Although no significant differences in survival rate were observed, fish infected at the lowest temperature showed a higher probability of death and delayed the mortality curve during the late stage of infection (35 days after infection). Thirty-three immunopathological biomarkers were identified for potential use in the search for a resistance phenotype for BKD, and eight were genes related specifically to the adaptive cell-mediated immune response.